The Effect of Health Service Quality on Patient Satisfaction Hospitalized of Malang Hospital - Silvia Intan Wardani; Ety Diana; Ivana Kusuma Widyawati (Universitas Mandala Waluya, 2022)
The two most important factors that affect hospital services are patient happiness and quality of service. Nurses, doctors who don't care about patients or their families, unpleasant doctors and nurses, and communication problems with medical staff are some of the hospital's medical services that patients don't like. This study aims to ascertain how the satisfaction of inpatients at Malang Hospital will be affected by medical service standards in 2022. This type of research is an analytical survey with an explanatory design. This population is inpatients using the BPJS general health service type and the sample is 68 people. Collect information with questionnaires or questionnaires. Univariate analysis, two-variable analysis using Pearson correlation, and multivariate analysis using multiple linear regression are examples of data analysis techniques. Bivariate results show that reliability is related to patient satisfaction. The results of multiple linear regression tests affecting patient satisfaction are reliability and care. Officers such as doctors and nurses need to be concerned in carrying out friendly services to patients to pay attention to patients and respond quickly to patient complaints.